Pragmatic utopias : ideals and communities, 1200-1630 - Horrox, Rosemary; Rees Jones, Sarah (Cambridge University Press, 2001)
This collection of essays was presented to Barrie Dobson in celebration of his 70th birthday. It will be welcomed by all scholars of pre-modern religion and society. Spanning the artificial divide between medieval and early modern, the contributors - all acknowledged experts in their field - pursue the ways in which men and women tried to put their ideals into practice, sometimes alone, but more commonly in the shared environment of cloister, college or city. The range of topics is testimony to the breadth of Barrie Dobson's own interests, but even more striking are the continuities and shared assumptions across time, and between the dissident and the impeccably orthodox. Taking the reader from a rural anchor-hold to the London of Thomas More, and from the greenwood of Robin Hood to the central law courts, this collection builds into a richly satisfying exploration of the search for perfection in an imperfect world.
Keywords: Christian sociology : England : History; England : Church history